DIGITAL APPROACHES IN LEGAL ENGLISH EDUCATION: BRIDGING TRADITION AND TECHNOLOGY - Danylchenko-Cherniak , Oksana (Studies in Comparative Education, 2024)
This article examines the growing role of English as an indicator of cross-border cooperation. The language is a powerful tool for communication, exchange of information and ideas, as well as for establishing connections and understanding between people from different cultural and ethnic backgrounds. In the context of globalisation and Ukraine’s integration into the global economic space, learning ESP is becoming not just an advantage, but an urgent need for professionals in any field. This article analyses the level of English proficiency according to the EF EPI. But it is important to note that it measures only a certain segment of the population (adults who took the test) and may not reflect the level of English proficiency in specific professional areas, such as the one you are focusing on. The development of a national strategy for ESP and securing funding for these programs are crucial state-level priorities. Universities face challenges in implementing quality ESP programs, including issues in teacher training, adapting curricula to industry needs and student skills, and ensuring sufficient resources, particularly funding. To enhance the effectiveness and competitiveness of ESP programs, alternative solutions such as online courses, seminars, language exchange programs, and government or industry initiatives should be considered, expanding opportunities beyond traditional university settings.